Health providers' perspectives on contraceptive use in rural Northwest Tanzania: A qualitative study - Christine Aristide; Brooke W. Bullington; Magdalena Kuguru; Radhika Sundararajan; Natalie T. Nguyen; Valencia J. Lambert; Agrey H. Mwakisole; Joyce Wamoyi; Jennifer A. Downs (Elsevier, 2022)
Objectives: In Tanzania, contraceptive use is limited, particularly in rural communities and even among women who would like to delay childbearing. This paper aims to present health providers' perspectives on populations seeking contraception and barriers that could be addressed to increase access to and uptake of contraception, given their interface with large portions of their communities. Study Design: We conducted 18 in-depth interviews with providers stationed at health dispensaries in six rural villages in northwest Tanzania. Two investigators independently coded interviews using a stepwise process to achieve consensus on prevalent topics. Results: Three topics emerged from our analysis: (1) nature of clients seeking contraception; (2) barriers to uptake of contraception; and (3) the role of secrecy in obtaining and using contraception. Health providers reported that married women with children were the most frequent users of contraception, alongside some single women, men, sex workers, and students. Barriers to contraception included lack of supplies and trained staff, misconceptions and fears, stigma, and unsupportive partners. Providers observed that contraception was often used secretly. They reported surreptitious visits and described clients' preferential use of discreet methods. Providers respected and supported clients' desires to keep visits confidential. Conclusion: Our data suggest maintaining high stocks of discreet contraceptive methods and deploying more trained staff to dispensaries could increase availability and access to contraceptives. At the community level, more education campaigns are warranted to address barriers, especially those related to stigma. Implications: Our work highlights the need for additional contraceptive methods that are easy to administer and discreet for women who must maintain secrecy. Future studies of the effectiveness of interventions and new contraceptives should obtain healthcare providers' perspectives, as they can provide important insights to service provision.